Alfabetização financeira: relações com fatores comportamentais e variáveis socioeconômicas e demográficas - Potrich, Ani Caroline Grigion (2016)
Financial literacy has been recognized as an essential skill for individuals to act in the complex economic context. However, the evidence indicates that financial literacy is a complex phenomenon that it can be determinant of other behavioral factors, besides presenting itself differently in different socioeconomic and demographic variables. Thus, the present research seeks to innovate and advance in this theme, aiming to develop a model capable of encompassing the direct and indirect relations of financial literacy with the behavioral factors: materialism, compulsive buying and propensity to debt. In addition to identifying the invariance of the proposed model according to the socioeconomic and demographic variables, when verifying if a single model is adequate to measure the financial literacy of different groups of individuals and to point out the differences of averages existing between them. For that, this research was carried out with 2,487 individuals, using confirmatory factorial analysis, structural equation modeling and multigroup analysis, with eight propositions and six research hypotheses that integrate the proposed model. The main results showed that the majority had a low level of financial literacy, and the model for their measurement was invariant only for the variables gender, schooling and own income, and confirming three research propositions. In addition, five research hypotheses were confirmed, showing that the impact of financial literacy on compulsory buying was the largest among the proposed direct relationships. The total effects that financial literacy has on behavioral factors, we can see that the greatest impact was on compulsive buying behavior, followed by the impact on the propensity to debt and, finally, on materialism. These results are important for the development of public policies and other actors interested in the theme, since financial literacy goes beyond the fact of impacting the financial health of those who have it, but it can also help in a broader way those who suffer of other psychosocial behaviors, such as compulsive buying behavior. Models of this theme become fundamental to understand the importance and possible impacts of adopting national financial literacy strategies, and it can help in the development of treatments. The results showed that the impact imagined when studying only the financial literacy in the propensity to debt of the individuals becomes even more expressive when other behavioral factors are involved in this relation.